Inspirasi dari Latompa dan Raimuna untuk Pembangunan Kawasan Transmigrasi Mutiara - Samsul Maarif; Ahmad Ilham Romadhoni; M. Azzam Al Haq; Syifa Oktavia; Zahra A. Nursyahida; Yulita K. Dewi; Mushtholikhul Fuad; Ignatius Dimas F.P. Pinilih (Direktorat Pengabdian kepada Masyarakat, 2023)
In an endeavour to support the development of the Mutiara Transmigration Area, the UGM KKN-PPM Team 2022-SG001 conducted community service activities in two villages in the Mutiara Area, namely Latompa Village and Raimuna Village, based on the Transmigration Area Development Index (IPKTrans) and the Human Development Index (HDI). The purpose of this article is to show programs that supported IPKtrans which are indicators of transmigration area development. This article is based on community-based research whose data collection methods included field observations, documentation, and interviews, as well as mapping the potential and problems observed in the field. The results showed that programs developed by the KKN-PPM UGM 2022-SG001 team in Latompa and Raimuna villages covered three of the five dimensions of IPKTrans, namely the economic, socio-cultural, and environmental dimensions. While related to the Human Development Index (HDI), the developed programs focused on two aspects, economy and health. Therefore, the community service program by the KKN-PPM UGM 2022-SG001 have supported to increase IPKTrans and the development of the Mutiara Region.